Survival in colon and rectal cancers in Finland and Sweden through 50 years - Hemminki, Kari; Försti, Asta; Hemminki, Akseli (BMJ open gastroenterology, 2021)
OBJECTIVES: Global survival studies have shown favourable development in colon and rectal cancers but few studies have considered extended periods or covered populations for which medical care is essentially free of charge. DESIGN: We analysed colon and rectal cancer survival in Finland and Sweden over a 50-year period (1967-2016) using data from the Nordcan database. In addition to the standard 1-year and 5-year survival rates, we calculated the difference between these as a novel measure of how well survival was maintained between years 1 and 5. RESULTS: Relative 1-year and 5-year survival rates have developed favourably without major shifts for men and women in both countries. For Finnish men, 1-year survival in colon cancer increased from 50% to 82%, and for rectal cancer from 62% to 85%. The Swedish survival was a few per cent unit better for 1-year survival but for 5-year survival the results were equal. Survival of female patients for both cancers was somewhat better than survival in men through 50 years. Overall the survival gains were higher in the early compared with the late follow-up periods, and were the smallest in the last 10 years. The difference between 1-year and 5-year survival in colon cancer was essentially unchanged over the 50-year period while in rectal cancer there was a large improvement. CONCLUSIONS: The gradual positive development in survival suggests a contribution by many small improvements rather than single breakthroughs. The improvement in 5-year survival in colon cancer was almost entirely driven by improvement in 1-year survival while in rectal cancer the positive development extended to survival past year 1, probably due to successful curative treatments. The current challenges are to reinvigorate the apparently stalled positive development and to extend them to old patients. For colon cancer, survival gains need to be extended past year 1 of diagnosis.
Keywords: Registries; Švédsko; kolon; Humans; Finland; registrace; Sweden; Female; Colon; lidé; nádory rekta; diagnostic and therapeutic endoscopy; Finsko; colorectal cancer; ženské pohlaví; Rectal Neoplasms; health service research; Male; mužské pohlaví